The Role of Personality and Subjective Exposure Experiences in Posttraumatic Stress Disorder and Depression Symptoms among Children Following Wenchuan Earthquake. Issue 1 (December 2017) - Chen, Xiacan; Xu, Jiajun; Li, Bin; Li, Na; Guo, Wanjun; Ran, Mao-Sheng; Zhang, Jun; Yang, Yanchun; Hu, Junmei
Abstract This study aims to investigate the role of personality traits and subjective exposure experiences in posttraumatic stress disorder and depression symptoms. In Qingchuan, 21, 652 children aged 7 to 15 years were assessed using face-to-face interviews one year after the Wenchuan earthquake in China. The Junior Eysenck Personality Questionnaire, a modified earthquake exposure scale, the UCLA Posttraumatic Stress Disorder Reaction Index (adolescent), and the Adolescent Depression Inventory were used to assess personality characteristics, trauma experiences, posttraumatic stress disorder and depression symptoms, respectively. The measurement was completed with 20, 749 children. After adjusting for other factors by multinomial logistic regression analysis, neuroticism, having felt unable to escape from the disaster and having been trapped for a longer time were risk factors of posttraumatic stress disorder and depression symptoms. Socialization was a protective factor of them. Having felt extreme panic or fear was a risk factor of posttraumatic stress disorder symptoms. For depression symptoms, introversion and psychoticism were risk factors, and extraversion was a protective factor. This study was conducted with the largest representative sample of child survivors of a natural, devastating disaster in a developing country. These results could be useful for planning psychological intervention strategies for children and for influencing further research.